Professionalism to Motivation: Mapping Key Determinants of Audit Quality in Government Institution Auditors - Deasy Emalia; Arifah, Dinda Zanubaloka; Vika Fitranita (LPPM Universitas Terbuka, 2025)
This research aimed to examine the effect of professionalism, independence, competence, and motivation on audit quality. The population in this study is the auditors of the Bengkulu Provincial government who work at Badan Pemeriksa Keuangan. This study used a purposive sampling method in selecting the sample, with the criteria of being an auditor of Badan Pemeriksa Keuangan at least 2 years. This research was conducted using a quantitative approach. Primary data were collected through a questionnaire containing a list of written questions regarding the influence of professionalism, independence, competence and motivation on Badan Pemeriksa Keuangan auditors in Bengkulu Province. To Analyze the independent variables against the dependent variable, a Smart Equation Modeling analysis by using the SmartPLS 3.0. The results showed that all of the independent variables have a positive influence on audit quality. Therefore, it recommends to create regulations that focus on human resource development, meaning that Badan Pemeriksa Keuangan needs to strengthen professionalism, maintain independence, improve competence, and motivate auditors.